2014
DOI: 10.1332/174426514x13990433991320
|View full text |Cite
|
Sign up to set email alerts
|

When does evidence-based policy turn into policy-based evidence? Configurations, contexts and mechanisms

Abstract: Many studies on evidence-based policy are still clinging to a linear model. Instead, we propose to understand expertise and evidence as ‘socially embedded’ in authority relations and cultural contexts. Policy-relevant facts are the result of an intensive and complex struggle for political and epistemic authority. This is especially true where science and policy are difficult to distinguish and the guidelines for validating knowledge are highly contested. To understand the mechanisms leading to policy-based evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(103 citation statements)
references
References 45 publications
0
98
0
5
Order By: Relevance
“…Our participants, for example, explained that infrastructural schemes were highly politicised and that in the current climate of financial austerity in the public sector, any business cases were increasingly reduced to an economic bottom line. It has been suggested that evidence in policy should be considered as “socially embedded in authority relations” [36], and that politics is not a third pillar besides research and policy but runs through all domains [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Our participants, for example, explained that infrastructural schemes were highly politicised and that in the current climate of financial austerity in the public sector, any business cases were increasingly reduced to an economic bottom line. It has been suggested that evidence in policy should be considered as “socially embedded in authority relations” [36], and that politics is not a third pillar besides research and policy but runs through all domains [30]. …”
Section: Discussionmentioning
confidence: 99%
“…In this context, this essay tries to disentangle the rhetoric with available empirical evidence to enable a more rational debate, at least in the discussion of policies, if not in the public arena. In recent years, the 'Evidence-Based Policy' (EBM) agenda has been challenged and the expression turned on its head by authors who talk about 'Policy-Based Evidence Making' (Sanderson, 2011;Strassheim & Kettunen, 2014;Torriti, 2010) ix . Critics argue that, even where facts are uncertain and values in dispute x , the EBP approach still relies on a-critical forms of empiricism and technocratic 'scientisation'…”
Section: Objectives Approach and Sourcesmentioning
confidence: 99%
“…Research evidence was later developed to support a policy already selected. The field of public health may be especially prone to the generation of “policy‐based evidence,” because of the pressure to make “science‐based” decisions under profound and often inescapable time constraints and because policy formation often occurs at the limits of existing knowledge . The impulse to take action may influence decision makers’ interpretations of the evidence, and perceptions of a need to protect credibility and deflect criticism may promote a tendency to find evidence that supports existing policies and to conceal conceptual doubts in the backstage…”
Section: Resultsmentioning
confidence: 99%